The effects of a minimum wage on employment outcomes an application of regression discontinuity design - Canales, Kristine Laura (2014)
In this paper, I ask whether a minimum wage increase results in adverse employment outcomes in terms of work hours and the probability of gaining or retaining employment. Regression discontinuity design (rdd) is employed on a household-level panel survey dataset, using the minimum wage as the forcing variable that determines whether a sample is assigned to either the treatment group (minimum wage worker) or the control group (above minimum wage worker). The rdd graphs and the regressions seem to point to a negative effect of a higher minimum wage on work hours, not only for workers earning the minimum wage but also for workers earning 50 percent more than the minimum wage. The probability of gaining/retaining employment is lower for minimum wage workers and for workers earning 50 percent above the minimum wage.
Keywords: Minimum wage; Labor market